Arabic Oratory and its Role in Development of Islamic Civilization in Seventh Century - Habib Mohamed Tahir Bijli (CV Media Inti Teknologi, 2026)
Background: Arabic oratory played a significant role in Arab civilization. With the advent of Islam, it changed significantly from tribal rhetoric to a tool for social control and moral guidance. But little is known about its use in early Islam as a civilizational communication mechanism.Objectives: This study looks at how, during the Prophetic and Rashidun eras, Arabic oratory supported societal cohesiveness, ethical development, and the legitimacy of government.Methods: Descriptive-analytical and hermeneutic techniques were used in a qualitative textual approach. Selected sermons (khutbah), sirah stories, and ancient rhetorical writings that were purposefully picked for their significance to ethics, governance, and communal identity made up the data. Thematic coding, interpretive analysis, and contextual reading were used to study the data.Results: The results demonstrate that Arabic oratory served as a fundamental channel for political legitimacy, communal integration, and moral internalization. Sermons facilitated the shift from tribal division to a morally cohesive ummah by transforming concepts of justice, accountability, and communal duty into common social standards.Conclusion: This study comes to the conclusion that early Islamic Arabic oratory was a civilizational infrastructure of communication rather than just a rhetorical tradition. Repositioning oratory as a strategic channel connecting revelation, ethics, and government in the development of Islamic culture is its scientific contribution.